SYSTEM OF EVENTS ON REPAIR AND MAINTENANCE OF MOTOR WAYS AND THEIR PLANNING - Zafar qizi, Qodirova Mahliyo (International Journal of Formal Education, 2024)
All existing classifications of road maintenance and repair work originate from the carriageway of the road, where the main road elements are pavement and road surface. Based on the condition of these elements, the period between repairs, the type of repair and the main work for each job are determined. The type and types of work for the remaining elements of the road are compared to the types of road maintenance and repair work. This approach was also preserved in the development of a new classification of road maintenance works, which provides information on the definition of tasks, tasks and scope of activities, criteria for each type of maintenance and repair of roads and road structures.